Performance Analysis of the Tukad Pakerisan South Denpasar Road Section Using the 2023 Indonesian Road Capacity Guidelines Method: Analisis Kinerja Ruas Jalan Tukad Pakerisan Denpasar Selatan Menggunakan Metode Pedoman Kapasitas Jalan Indonesia 2023 - Luh Putu Merta Karunia Putri; I Gede Fery Surya Tapa; I Putu Kresna Suputra; Carolina Susana Putri Nahak; Putu Ariawan; Putu Budiarnaya (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
This study analyze the performance of the existing condition the Tukad Pakerisan road section, as well as the projected performance of the road section for the next 5 years. The method uses the 2023 Indonesian Road Capacity Guidelines (PKJI) method. Data were collected through a survey 2 weekdays and 2 weekend days for 12 hours, which was conducted on two road segments road section. The analysis show that the traffic flow volume on segment A is 2025.45 pcu/hour and B is 1865.65 pcu/hour, the road capacity on segment A is 1877.669 pcu/hour and B is 1671.583 pcu/hour, and the degree of saturation on segment A reaches 1.08 and segment B reaches 1.12, which indicates that the road condition is at service level F, meaning it is experiencing severe congestion. Performance projections for the next five years indicate that the degree of saturation is expected to continue to increase beyond the acceptable limit of the degree of saturation set in the 2023 PKJI, which is 0.85. The results that the Tukad Pakerisan road section requires traffic engineering related to traffic diversion during peak hour and  recommends the addition of traffic signs and the implementation of traffic engineering to reduce congestion.